Synthesis of benzamide derivatives and evaluation of their in vitro and in silico tyrosinase inhibitory activities - Tran Hoai Tu; Nguyen Trung Nhan; Dang Hoang Phu (Vietnam Journal of Science and Technology, 2024)
In this research, six benzamide derivatives were traditionally synthesized using hydrazine, carbazide, and hydroxylamine derivatives through the pre- or in situ activation of the carboxylic acid functionality. Their chemical structures were identified as N′-phenylbenzohydrazide, N′-(2,4-dinitrophenyl)benzohydrazide, N′-(benzoyloxy)benzamide, N-dibenzoylurea, 2-amino-5-(4-phenyl)-1,3,4-thiadiazole, and benzohydrazide based on the interpretation of NMR spectroscopic data. Among these products, N′-phenylbenzohydrazide and N-(benzoyloxy)benzamide showed potent tyrosinase inhibitory activity with the IC50 values of 10.5 and 2.5 μM, respectively, stronger than that of kojic acid (44.6 μM). Docking studies between oxy-tyrosinase and the two active compounds have been carried out to analyze their binding interactions. Both two active compounds showed negative binding free energy values (S values) and some more interactions than the positive control (kojic acid). This discovery provided evidence for the potent tyrosinase inhibitory activity of these two compounds, making them promising candidates for the development of anti-tyrosinase agents in medicine and cosmetics.